Dry-Aged Beef Steaks: Effect of Dietary Supplementation with Pinus taeda Hydrolyzed Lignin on Sensory Profile, Colorimetric and Oxidative Stability - Aristide Maggiolino; Maria Federica Sgarro; Giuseppe Natrella; Josè Manuel Lorenzo; Annamaria Colucci; Michele Faccia; Pasquale De Palo (Foods, 2021)
Flavor is one of the main factors involved in consumer meat-purchasing decision and use of natural antioxidants in animal feeding had a great appeal for consumers. The aim of this trial is to evaluate the effect of Pinus taeda hydrolyzed lignin (PTHL) feed addition on oxidative stability, volatile compounds characteristics, and sensory attributes of 35 days dry-aged beef steaks. Forty steer six months old were randomly divided into a control group (CON; n = 20) and an experimental group (PTHL; n = 20). Both groups were fed ad libitum for 120 days with the same TMR and only the PTHL group received PTHL supplement. Samples of LT muscle were removed from carcasses and dry aged for 35 days at 2 °C, 82% of humidity, and 0.4 m/s of ventilation and then analyzed. Meat of CON group showed lower yellowness (p < 0.01) and higher TBARS (p < 0.01) values. Moreover, CON meat showed higher volatile aldehydes and lower sulfur compounds (p < 0.01), with higher unpleasant odor (p < 0.05) and meaty odor (p < 0.01) score revealed by sensory assessors. PTHL inclusion in beef diet delayed the oxidative mechanisms in 35 days dry-aged steaks, resulting in an improved colorimetric, volatolomic, and sensory profile.